Left Ventricular Pseudoaneurysm after Aortic Valve Bypass Implantation. Issue 9 (26th May 2015) - Søholm, Helle; Hassager, Christian; Vejlstrup, Niels; Arendrup, Henrik; Jensen, Maiken; Lund, Jens; Ihlemann, Nikolaj
Mini‐Abstract Aortic valve bypass (AVB)—a conduit from the apex of the left ventricle to the descending aorta containing a bioprosthetic valve—is a treatment option in severe aortic stenosis unsuitable for both surgical aortic valve replacement and transcatheter aortic valve replacement. An 82‐year‐old woman with severe aortic stenosis, porcelain aorta, and limited vascular access had an AVB inserted successfully. Imaging 3 months after implantation revealed a pseudoaneurysm at the AVB insertion site. Due to comorbidity and advanced age, the patient has been treated conservatively. Procedures with transapical insertions such as TAVI or AVB can lead to pseudoaneurysms, and the diagnosis often requires multiple imaging modalities.